2020
DOI: 10.1007/s11230-020-09926-4
|View full text |Cite
|
Sign up to set email alerts
|

Retroporomonorchis pansho n. g., n. sp., an unusual monorchiid trematode exploiting an atypical host

Abstract: The Monorchiidae Odhner, 1911 are well represented in tropical and subtropical marine fishes worldwide but rarely reported from the Lutjanidae, an important family of tropical fishes that prey mainly on demersal fishes, decapods and cephalopods. Here, we report the first monorchiid from a lutjanid in Australian waters, Retroporomonorchis pansho n. g., n. sp. in Lutjanus fulvus (Forster), off Lizard Island on the northern Great Barrier Reef. It is morphologically and phylogenetically distinct among known monorc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Wee et al . (2020 a ) observed that most reports of monorchiid infections in lutjanid fishes are unconvincing; just two are well-supported with evidence. Wee et al .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Wee et al . (2020 a ) observed that most reports of monorchiid infections in lutjanid fishes are unconvincing; just two are well-supported with evidence. Wee et al .…”
Section: Discussionmentioning
confidence: 91%
“…Sciaenid fishes are significantly less parasitized by monorchiids; to our knowledge, 10 species of monorchiids from five genera have been reported from the family, with a single species of Helicometroides, H. leiperi, reported only from O. ruber (see Ahmad, 1982). Wee et al (2020a) observed that most reports of monorchiid infections in lutjanid fishes are unconvincing; just two are well-supported with evidence. Wee et al (2020a) suggested that the two lutjanids reported as hosts of H. pseudovitellosus (see Madhavi, 1974) and H. vitellosus (see Durio and Manter, 1968) were likely haemulids as neither host was identified to species, lutjanids are easily confusable with haemulids, and as species of Helicometroides are known overwhelmingly from haemulids.…”
Section: Key To the Species Of Helicometroidesmentioning
confidence: 88%
See 2 more Smart Citations
“…Monorchiids are morphologically characterised by complex terminal genitalia armed with recurved spines, vitelline follicles in restricted fields, and well-developed uterine coils [11]. The genetic library for species allocated to the family has increased significantly in the recent years; several new species have been described following an integrative taxonomy approach, most of them from Australian marine fish [18,[25][26][27][29][30][31]. In a recent study, Wee et al [28] performed one of the most comprehensive studies for species in the genus Lasiotocus Looss 1907, a taxonomically problematic group within the Monorchiidae.…”
Section: Introductionmentioning
confidence: 99%